1988
DOI: 10.1128/iai.56.9.2417-2423.1988
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an adhesion antigen of Streptococcus sanguis G9B

Abstract: An antigen possessing the attributes of an adhesin has been identified in Streptococcus sanguis G9B. Cell surface components were extracted from G9B and a spontaneously occurring nonadherent mutant of G9B, strain Adh-, with a 2 mM barbital buffer, pH 8.6. The extract of G9B but not of Adh-absorbed more than 80% of the adhesion-inhibitory activity of anti-G9B immunoglobulin G (IgG). Immunoblots revealed 80-and 52-kilodalton (kDa) antigens present in the G9B extract but not in the Adhextract. Absorption of anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…All of the studies reported here used the same pools of antisera and the IgG derived from these pools. Mouse anti-80-kDa serum was prepared using essentially the same protocol described previously for rabbit anti-80-kDa serum (24,25), In brief barbital extracts of G9B were subjected to SDS-PAGE (see below) and the 80-kDa band was eut out of the gel, macerated in 0.15 NaCI and mixed with an equal volume (ca. 0.2 ml) of Freund's complete adjuvant.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…All of the studies reported here used the same pools of antisera and the IgG derived from these pools. Mouse anti-80-kDa serum was prepared using essentially the same protocol described previously for rabbit anti-80-kDa serum (24,25), In brief barbital extracts of G9B were subjected to SDS-PAGE (see below) and the 80-kDa band was eut out of the gel, macerated in 0.15 NaCI and mixed with an equal volume (ca. 0.2 ml) of Freund's complete adjuvant.…”
Section: Methodsmentioning
confidence: 99%
“…The second dimension used 6,7 ml agar'ose and was run at 2.4 V/cm for 18 h on a glass plate cooled to 4 C. The gels wer'e washed in saline, dried, stained with Coornassie Brilliant Blue (CBB) and destained prior to photography (3), Quantitation of the antigen was performed by estimating the height of the rockets (22). In some studies an intermediate gel containing an affinity purified antibody against the 80 kDa antigen complex (25) was inserted between the first and second dimension.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations